Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/nleng-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal radiation and chemical reaction effects on boundary layer slip flow and melting heat transfer of nanofluid induced by a nonlinear stretching sheet

Abstract: A theoretically investigation has been performed to study the effects of thermal radiation and chemical reaction on MHD velocity slip boundary layer flow and melting heat transfer of nanofluid induced by a nonlinear stretching sheet. The Brownian motion and thermophoresis effects are incorporated in the present nanofluid model. A set of proper similarity variables is used to reduce the governing equations into a system of nonlinear ordinary differential equations. An efficient numerical method like Runge-Kutta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Mabood et al and Nawaz et al also noted the same trend. A reversal effect on temperature with regard to higher values of the radiation parameter Nr is noted, as illustrated in Figure , and it may be explained by the fact that the impact of thermal radiation causes a reduction in the energy transport rate to the ambient fluid resulting in lower temperatures, as observed by Mabood et al and Krishnamurthy et al…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Mabood et al and Nawaz et al also noted the same trend. A reversal effect on temperature with regard to higher values of the radiation parameter Nr is noted, as illustrated in Figure , and it may be explained by the fact that the impact of thermal radiation causes a reduction in the energy transport rate to the ambient fluid resulting in lower temperatures, as observed by Mabood et al and Krishnamurthy et al…”
Section: Resultsmentioning
confidence: 55%
“…Consequently, less heat is transferred from the ambient fluid to the melting surface leading to higher temperature. Mabood et al 28 reversal effect on temperature with regard to higher values of the radiation parameter Nr is noted, as illustrated in Figure 13, and it may be explained by the fact that the impact of thermal radiation causes a reduction in the energy transport rate to the ambient fluid resulting in lower temperatures, as observed by Mabood et al 27 and Krishnamurthy et al 39 It is seen from Figure 14 that increasing values of the melting heat transfer parameter diminish the temperature as melting causes the heat transfer from the fluid to the surface and thus the fluid gets cooled. From Figure 15, it is found that the temperature enhances significantly with increasing values of Eckert number (Ec).…”
mentioning
confidence: 69%
“…Yazdi et al (2014) reported the steady slip boundary layer flow and heat transfer of a non-Newtonian power-law fluid over continuously nonlinear moving permeable surface at prescribed surface temperature including the effects of viscous dissipation and internal heat generation/absorption. Krishnamurthy et al (2016) examined the thermal radiation and chemical reaction effect on MHD velocity slip boundary layer flow and melting heat transfer of nanofluid induced by a nonlinear stretching heet. Raju et al (2016) analyzed the flow, heat and mass transfer behavior of Casson fluid past an exponentially permeable stretching surface in presence of thermal radiation, magnetic field, viscous dissipation, heat source and chemical reaction.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Ramesh et al (2015Ramesh et al ( , 2016 numerically investigated heat transfer problems with stretching sheet for variable thickness and convective boundary layer in the latter study. Krishnamurthy et al (2016) investigated the effect of thermal radiation on melting heat transfer of nanofluid with nonlinear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%